Explorando a internet das coisas sociais utilizando NFC em um campus universitário - Alves, Tiago Marcos (Universidade do Vale do Rio dos Sinos, 2015)
The Internet of Things (IoT) allows the interconnection of smart objects, such as smartphones, tablets, televisions and wireless sensors, with humans, using different communication protocols through the development of a heterogeneous multi-modal dynamic network. In this sense the convergence of IoT technology with the concept of social networks has given rise to a paradigm called Internet of Things Social (SIoT). In SIoT objects mimic behaviors of humans and create their own relationships based on rules established by its owners. In this context, this paper proposes the provision of a social network that explore the concepts of SIoT using Near Field Communication (NFC) technology. The proposed model defines a platform to handle communication of smart objects on a college campus for the benefit of students, teachers and other participants from the academic community. In this model, the definition of the smart objects are objects that provide functionality for interacting with humans, such as smartphones, tablet, refrigerators and televisions. As a scientific contribution this paper proposes a social network for smart objects with application in a university setting, based on the approach of SIoT. The model, called SIoTCampus, focuses on the use of several existing objects on a college campus, suggesting a relationship between these in order to be a new tool to disseminate information among the members of the university community, including faculty, staff, students and visitors. Among the existing scenarios of unique applications for SIoT, it was not observed an application for this kind of focused relationship to a college campus. Thus the proposal of SIoTCampus model is an exclusive social network for smart objects in an academic environment in which context information such as location, calendar, etc. are used as criteria for establishing relationships between intelligent devices. Initial settings on preferences of owners are informed in this model in a mobile application developed for this function. So specific information about certain subjects, published events, relevant news certain topics on a college campus, which are captured by these objects are sent to a server and analyzed so that this information may or may not be used to establish relationships between these objects. The results of this work showed a communications architecture that sought to deal with the possible relationships between intelligent objects present at the university. The assessment of this work was done through the use of scenarios to explore the main idea here is that described the relationship between Smart Objects. Some scenarios for this assessment were implemented and applied to a group of students of Computer Science Course of the Universidad do Vale do Rio dos Sinos. Among the results we highlight that for 80% of users who participated in this evaluation found that the model can become an important integration tool among members of the academic campus. Another important point highlighted to the participants profile of this evaluation was that the use of NFC technology expands the model of using possibilities. This is justified due to new forms of interaction between devices of users that could be met by the use of this technology.
Keywords: Internet social das coisas; Internet das coisas; NFC; Computação móvel; Ciência de contexto; Mobile computing; Context awareness; Internet of things; Social internet of things; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação